Structural basis of ER-associated protein degradation mediated by the Hrd1 ubiquitin ligase complex - Wu, Xudong; Siggel, Marc; Ovchinnikov, Sergey; Mi, Wei; Svetlov, Vladimir; Nudler, Evgeny; Liao, Maofu; Hummer, Gerhard; Rapoport, Tom A. (Science (American Association for the Advancement of Science), 2020)
Misfolded endoplasmic reticulum (ER) proteins are retrotranslocated into the cytosol, polyubiquitinated, and degraded by the proteasome in a process known as ER-associated protein degradation (ERAD). ERAD of misfolded luminal ER proteins (ERAD-L) is mediated by the Hrd1 complex, composed of the ubiquitin ligase Hrd1 and four additional proteins (Hrd3, Der1, Usa1, and Yos9). Wu et al. report a cryo–electron microscopy structure of the active Hrd1 complex from yeast and, based on this structure, developed a model for how substrates are recognized and retrotranslocated. They propose that Hrd3 and Yos9 jointly create a luminal binding site for misfolded glycoproteins. Hrd1 and Der1 form “half-channels” juxtaposed in a thinned section of the ER membrane, which allows a polypeptide loop of an ERAD-L substrate to move through it. Science , this issue p. eaaz2449 The Hrd1 complex retrotranslocates misfolded luminal endoplasmic reticulum proteins through “half-channels” juxtaposed in a thinned membrane. Misfolded luminal endoplasmic reticulum (ER) proteins undergo ER-associated degradation (ERAD-L): They are retrotranslocated into the cytosol, polyubiquitinated, and degraded by the proteasome. ERAD-L is mediated by the Hrd1 complex (composed of Hrd1, Hrd3, Der1, Usa1, and Yos9), but the mechanism of retrotranslocation remains mysterious. Here, we report a structure of the active Hrd1 complex, as determined by cryo–electron microscopy analysis of two subcomplexes. Hrd3 and Yos9 jointly create a luminal binding site that recognizes glycosylated substrates. Hrd1 and the rhomboid-like Der1 protein form two “half-channels” with cytosolic and luminal cavities, respectively, and lateral gates facing one another in a thinned membrane region. These structures, along with crosslinking and molecular dynamics simulation results, suggest how a polypeptide loop of an ERAD-L substrate moves through the ER membrane.